Organization of research activities as a way to develop undergraduates’ functional literacy - Irina A. Pushkareva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper considers the development of functional literacy and its structural components in the process of organizing the research activities of undergraduates in the process of mastering the discipline «Foreign Language in Law». Assessment of the level of development of the components under consideration was carried out at each stage of the students’ activities. The objects of assessment were the demonstrated skills and abilities of undergraduates. As an urgent trend in the modernization of modern education, the development of functional literacy is analyzed at the level of vocational education. Special attention is paid to functional literacy as the basis of foreign-language communicative competence, implemented in solving practical problems of academic and professional interaction. The effectiveness of the organization of research activities in order to develop the functional literacy of undergraduates is due to a system of interconnected didactic principles of training and is confirmed by high personal, subject and meta-subject results.